Restorative Justice for Young Offenders: An Analysis of the French Circular Confronting a European and National Legal Perspective - Jessica Filippi (UCL Journal of Law and Jurisprudence, 2018)
This article is a critical analysis of the new French circular of the 15 March 2017 (‘the 2017 Circular’), which deals with the implementation of restorative justice in France especially in the field of juvenile justice.The analysis of ‘the 2017 Circular’ is made in comparison with the background of the European Directive on Juvenile Justice and the international literature concerning criminological processes in restorative justice (more precisely the principles of restorative justice). This article will demonstrate that restorative justice and the philosophy it is based on (restorative justice principles) are in line with the European Directive 2016/800, which deals with child participation in juvenile justice and child-friendly justice.However, this European Directive is not mentioned in the French circular. Not mentioning it could be interpreted as a way to make explicit the importance of the welfare model in juvenile justice in relation to the possible ways for a juvenile to participate actively in justice through restorative justice. Then, this article will undertake a critical analysis to identify the gaps between the philosophical principles on which restorative justice is founded and their implementation in the French legal framework and the circular previously mentioned. It will also propose some clarifications in the use of legal terms to better conform to the philosophy and the processes of restorative justice. For full text, please click here
Keywords: France; criminal justice; penal law; young offender